CHOROIDAL MELANOMA IN A PATIENT WITH WAARDENBURG SYNDROME. Issue Volume 9:Issues 4(2015:Autumn) (2015) - Itty, Sujit; Richter, Elizabeth R.; McCannel, Tara A.
Abstract : Purpose: To report a case of choroidal malignant melanoma in a patient with Waardenburg syndrome and bilateral choroidal pigmentary abnormalities. Methods: Clinical examination and multimodal imaging of the case. Results: A 45-year-old woman presented with asymptomatic flat choroidal pigmentation abnormalities in both eyes. A choroidal lesion was identified in the inferotemporal periphery of the left eye arising from an area of hyperpigmentation; ultrasonography findings were consistent with a choroidal melanoma. The patient endorsed a personal and family history of premature graying of hair and was identified to have dystopia canthorum consistent with the diagnosis of Waardenburg syndrome. Conclusion: The authors present the first reported case of concurrent Waardenburg syndrome and choroidal malignant melanoma. This cooccurrence may suggest that the relative hyperpigmented regions in affected fundi may be abnormal and should be monitored closely for the development of choroidal melanoma. Abstract : A 45-year-old woman with premature graying of hair and dystopia canthorum was found to have bilateral choroidal melanocytosis and a choroidal melanoma in the left eye. Multimodal widefield imaging of this first reported case of concurrent Waardenburg syndrome and choroidal melanoma is presented.